Deformation Pattern of the Northern Sector of the Malta Escarpment (Offshore SE Sicily, Italy): Fault Dimension, Slip Prediction, and Seismotectonic Implications - Gambino, Salvatore; Barreca, Giovanni; Gross, Felix; Monaco, Carmelo; Krastel, Sebastian; Gutscher, Marc-André (Frontiers in Earth Science, 2021)
Marine seismic reflection data coupled with on-land structural measurements improve our knowledge about the active deformation pattern of the northern sector of the Malta Escarpment, a bathymetric and structural discontinuity in the near-offshore of Eastern Sicily. As favourably oriented to be reactivated within the Neogene Africa–Europe convergence, it is believed that the Malta Escarpment has a significant role in the recent seismotectonic framework of the Western Ionian Basin and the Hyblean foreland domain of SE Sicily, where some of the largest and most destructive Mediterranean earthquakes are located according to available historical catalogs. Offshore seismic data along with bathymetric grids illuminate the shallow subseafloor setting and allow more accurate mapping of the seafloor expression of previously identified faults in the area. The seismic interpretation and the near-fault sediment pattern analysis provide constraints on fault 3D geometries as well as on their through-time tectonic activity, suggesting also that part of the observed deformation may have been caused by nontectonic processes. Identified faults form currently an E-dipping, roughly N–S trending, and 60 km-long extensional belt deforming the seafloor with a significant displacement amount in the Ionian offshore between Catania and Siracusa. 3-dimensional parameters of faults were then used to derive expected magnitudes and their reactivation propensity. Empirical scaling relationships and forward methods point to a high seismic potential for the detected fault as well as predict the fault slip behavior according to the field-derived differential stress. This combined analysis along with faults displacement measurements pointed out how the longest and most continuous fault could be capable of generating M > 7 seismic events, putting forward strong seismotectonic implications for the adjacent and densely populated Hyblean Plateau. The expected magnitude and the estimated recurrence time interval are compatible with those inferred for large historical earthquakes in the area even if other offshore seismic sources cannot be ruled out.